Controllable Fabrication of Core‐Shell Co9S8/Co Embedded on Multi‐Channel Carbon Nanofibers as Efficient Oxygen Electrocatalysts for Rechargeable Zn‐air Batteries. Issue 17 (9th July 2021) - Tang, Zeming; Nie, Zhongxiang; Yuan, Meichen; Lai, Qingxue; Liang, Yanyu
Abstract: Designing bifunctional electrocatalytic sites with outstanding activity and durability in one component toward oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is quite essential for rechargeable Zn‐air batteries. Herein, a novel core‐shell composition of Co9 S8 /Co embedded multi‐channel carbon nanofiber was successfully developed as efficient electrocatalysts for ORR and OER by step pyrolysis. The precursor of polystyrene was degraded while polyacrylonitrile was cross‐linked to hexatomic ring during the pro‐oxidation process, therefore, endowing the longitudinal and parallel channels along the fibers' skeleton in the subsequent carbothermal reduction steps, which affords the superhighway for competent mass transmission and outstanding electrochemical specific area. On the other hand, the potent synergistic effect from precision‐designed core–shell species of Co9 S8 /Co allows the composite multi‐channel carbon fiber excellent ORR/OER bifunctional catalytic activities, with a gap of 0.89 V between the half‐wave potential toward ORR and potential of OER at a current density of 10 mA/cm 2 . Additionally, the rechargeable Zn‐air batteries were capable of operating steadily over 500 discharging/charging cycles at a constant current density of 5 mA/cm 2 . Abstract : Integrated construction of high‐throughput multi‐channel carbon nanofibers and high‐activity bifunctional catalyst (core‐shell Co9 S8 /Co) is realized through step pyrolysis by utilizing the thermal differences in the fiber precursor's components. The obtained Co9 S8 /Co‐MCCNFs demonstrated excellent cycle stability of charge‐discharge in zinc‐air batteries.